The Relationship Between Of Online Learning With Student Character - Nakata, Yua Nagami; Yelfi, Reno (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
This study aims to describe the online learning knowledge possessed by students, describe student character and analyze whether there is a relationship between online learning during the Covid-19 pandemic to the character of grade XII students Food Services at SMKN 9 Padang. This research method is quantitative, with a correlational approach. The results showed that the category of respondents' achievement level (TCR) of online learning was 3.64 with a high category and the respondents' achievement level (TCR) of student character was 3.05 with a medium category. There is a significant relationship between online learning during the Covid-19 pandemic and the character of class XII Boga Services students at SMKN 9 Padang.